Increasing ratio of coliform and hemolytic bacteria to total bacterial load of Bhojtal – A serious concern - Mishra, Anita; Shende, Kishor; Gothalwal, Ragini (Recent Research in Science and Technology, 2013)
Water temperature has great influence on bacterial population. Seasonal change in temperature and other anthropogenic activities greatly influences the bacterial population. The ratio of counts of fecal coliform to total coliform has been proposed as mean to differentiating between contamination from human and animal sources. Bhojtal (Bhopal MP India) is main source of potable water to Bhopal city. Average water temperatures of upper lake were 290-300 C, 240-250 C and 170-180 C during summer, monsoon and winter respectively. Study was performed during the three seasons of the year 2010 to 2012, on three different media. Coliform and haemolytic bacterial loads were statistically analyzed for the influence of season and sampling sites. Significantly high CFU values were observed at all three sites during summer season. Significant variation was observed only between the Hammidia hospital site and other two sites (Bairagarh and Prempura), as compared to that of Prempura and Bairagarh sites. The ratio of coliform and hemolytic bacteria to total bacterial population was around 0.43 – 0.51 and 0.25 – 0.42 respectively during 2010-11 and this ratio was increased during 2011-12, as 0.45 – 0.55 and 0.31 – 0.47 respectively. Total coliform count and hemolytic bacteria were comparatively higher in 2011-12 than 2010-11, specifically at the site receiving sewage from densely populated area and also due to the interference of high human induced activities. It can be concluded that variation in coliform and hemolytic bacterial population is significantly influenced by seasonal temperature variation and mainly due to anthropogenic activities and sewage with high load of fecal coliform.